Compliance with the rules for protecting hazardous work areas at the construction site through the use of inventory, mass-produced protection means - Chertkov О. (Ways to Improve Construction Efficiency, 2019)
Among accidents occurring in construction, the fall of workers from a height of 30%. Although employers, construction managers and occupational safety and security officials are directly responsible for the proper organization of the production process and the creation of appropriate conditions for protecting workers from the effects of harmful and dangerous factors, construction often occurs as a violation of the rules of the fence hazardous work areas, and mistakes when constructing temporary gangways and bridges for passing people and others. These violations and errors could have been avoided if: a. differentiation, typing and qualification of measures and means for protecting workers from falling from height, by developing collections of standard technological maps and assemblies for various types of construction and construction work; b. a directory of manufacturers and suppliers of tools to protect workers from falling from a height was created.